Compostos voláteis da polpa de maracujá (Passiflora edulis F. Flavicarpa) orgânica e convencional - Macoris, Mariana Serrao [UNESP]; Janzantti, Natalia Soares [UNESP]; Garruti, Deborah dos Santos; Monteiro, Magali [UNESP] (FapUNIFESP (SciELO), 2011)
The volatile compositions from organic and conventional passion fruit pulps produced in Brazil were investigated. The pulps were also physicochemically characterized. The volatile compounds from the headspace of the passion fruit pulp were stripped to a Porapak Q trap for 2 hours; they were eluted with 300 μL of dichloromethane, separated by gas chromatography/flame ionisation detection and identified through gas chromatography/mass spectrometry. Both pulps conformed to the requirements of the Brazilian legislation, indicating they were suitable to be industrialized and consumed. A total of 77 compounds were detected in the headspace of the passion fruit pulps - 60 of which were identified, comprising 91% of the total chromatogram area. The major compounds were the following: ethyl butanoate, 52% and 57% of the total relative area of the chromatogram for the organic and conventional passion fruit pulps, respectively; ethyl hexanoate, 22% and 9%, respectively; and hexyl butanoate, 2% and 5%, respectively. The aroma of the organic passion fruit pulp is mainly related to the following volatile compounds: ethyl hexanoate, methyl hexanoate, β-myrcene and D-limonene. The conventional passion fruit pulp presented methyl butanoate, butyl acetate, hexanal, 1-butanol, butyl butanoate, trans-3-hexenyl acetate, cis-3-hexen-1-ol, butyl hexanoate, hexyl butanoate, 3-hexenyl butanoate and 3-hexenyl hexanoate as the main volatile compounds for aroma.
Volatile compounds from organic and conventional passion fruit (Passiflora edulis F. Flavicarpa) pulp
Keywords: Aroma; Flavor chemistry; Fruit pulp; Gas chromatography/mass spectrometry; Organic passion fruit